2015
DOI: 10.1159/000439531
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Haplogroup R Confers a Genetic Risk Factor for Intrauterine Adhesion in Han Women Population

Abstract: Background: To determine whether a specific mitochondrial DNA (mtDNA) haplogroup is implicated in the pathogenesis of intrauterine adhesion (IUA). Methods: Peripheral blood samples were collected from 486 women with (case group, n = 154) and without IUA (control group, n = 332) at the Women's Hospital, Zhejiang University School of Medicine. Genomic DNA was extracted from the blood, and the mtDNA haplogroups of Han women M, N and R were determined by sequencing hypervariable mtDNA segments and testing diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Lysosomal hydrolase release and lysosomal dysfunction are found in endometrial stromal cells, which may lead to mitochondrial dysfunction [21] . Our previous studies on mitochondrial DNA also found that the polymorphism of genes that transcribe and translate proteins related to oxidative phosphorylation in mitochondrial DNA can affect the repair and proliferation of the endometrium, which indirectly con rmed that the change of mitochondrial function is related to the repair and proliferation of the endometrium [22] .…”
Section: Discussionmentioning
confidence: 78%
“…Lysosomal hydrolase release and lysosomal dysfunction are found in endometrial stromal cells, which may lead to mitochondrial dysfunction [21] . Our previous studies on mitochondrial DNA also found that the polymorphism of genes that transcribe and translate proteins related to oxidative phosphorylation in mitochondrial DNA can affect the repair and proliferation of the endometrium, which indirectly con rmed that the change of mitochondrial function is related to the repair and proliferation of the endometrium [22] .…”
Section: Discussionmentioning
confidence: 78%
“…Pathogenesis of IUA remains unknown although there are several hypotheses on this, including active proliferation of fiber cells (10) and neural reflection (3). The risks of IUAs are abortions, pelvic inflammatory disease, IUD related intrauterine diseases, other intrauterine diseases and genetic inheritance (11)(12)(13)(14). Hysteroscopic surgery is the gold standard for the diagnosis and treatment of IUA.…”
Section: Perplexity For the Treatment Of Iuasmentioning
confidence: 99%